Jak dotrzeć do zrozumienia tekstu literackiego? Kilka refleksji na temat Ballady Pani Twardowska Adama Mickiewicza w odbiorze uczniów Polskich I Cudzoziemskich - Socha, Magdalena (Slavia Occidentalis, 2024)
The aim of my thesis is to reflect on Pani Twardowska, a literary text written by Adam Mickiewicz, and how Polish and foreign students receive and understand this text by. Its language and interpretation pose a challenge to students and teachers. An analysis of the ballad which is assigned reading, shows difficult fragments because of failure to recognize the various aspects of the language. It also leads to considering a practice of working with an old literary text that serves as a representative of an old era language and an exponent of culture. The considerations are accompanied by a question of possible use of glottodidactic methods to support an analysis and interpretation of a literary text during Polish classed conducted in a linguistically and culturally diverse group of students.